Passive sentinel surveillance system for sexually transmitted diseases in primary healthcare sites in Ethiopia, 1991–3. Issue 2 (1st April 2000) - Matteelli, A; Kassa, A; Gerbase, A; Farina, C; Ghidinelli, M; Chatel, G; Beltrame, A; Feleke, W; Carosi, G
Abstract : Background: In 1989 the ministry of health of Ethiopia launched an STD control programme to strengthen the STD case management capabilities at public health centres and hospitals. The programme included the introduction of a syndrome based system for notification of STD cases. We here report the data originated by the syndromic case reporting system under programme conditions. Methods: 35 (17%) of the total 225 hospitals and public health centres of Ethiopia were included in the programme. Information relevant to the years 1991 to 1993 was analysed at mid 1994. Results: 32 clinical sites (91% of the total) provided at least one monthly report. The proportion of monthly reports received was 65% of those due, ranging from 51% in 1991 to 73% in 1992 and 42% in 1993. A total of 77 294 consultations for STD related symptoms were recorded, including 70 200 new cases, 6588 repeated consultations, and 506 partners of STD patients. Among first attendant patients 38 459 (52.7%) were males with a male to female ratio of 1:1. Urethral discharge and vaginal discharge were the leading cause of consultation among males (58%) and females (64%) respectively. The frequency of genital ulcer diseases was 26% among males and 15% among females. Inguinal adenopathy in the absence of genital ulcers was also frequent, accounting for 10% of consulting males and 5% of females. Based on Gram stain, gonorrhoea was identified in 64% of the cases of urethral discharge, while trichomoniasis and candidiasis were identified by wet mount in 28% and 16% of the cases of vaginal discharge respectively. Conclusions: STDs are a common cause of consultation at public health centre sites in Ethiopia. A syndromic case reporting system proved to be efficient and produced valuable information to initiate assessment of the problem and to set up bases for monitoring trends of STD morbidity.